The Influence Of Instagram And Tourist Attractions On Visiting Decisions To Agro-Tourism Sirah Kencong Blitar - Kusuma, Agung Hendra; Zamrodah, Yuhanin; Kurniastuti, Tri; Oryza Sativa, Rima Dewi (Universitas Djuanda, 2025)
The background underlying this research is fluctuating visit data. Obtained through PT Perkebunan Nusantara I Regional 5. The purpose of knowing the effect of Instagram and tourist attraction on the decision to visit tourists to Agro Sirah Kencong Tourism Blitar partially or simultaneously. Quantitative explanatory research type. The research sample is tourists who visit Sirah Kencong Agro Tourism Blitar in accordance with the criteria. Probability sampling method and accidental sampling technique (n = 110). The questionnaires used were Instagram social media, tourist attractions, and tourist visiting decisions. Statistical tests in the form of multiple linear regression with partial test results (t) on variable X1 0.051> 0.05 there is no influence on variable Y and variable X2 0.000 <0.05 there is an influence on variable Y, while the simultaneous test (F) sig. 0.000 <0.05, which if taken as a conclusion, variables X1 and X2 have a significant influence on variable Y. The conclusion of this study is that variable X1 Instagram social media has no partial effect on tourist visiting decisions, variable X2 tourist attraction has a partial effect on visiting decisions, and X1 and X2 have simultaneous influence on the decision to visit tourists to Sirah Kencong Agro Tourism.